How do political elements affect agricultural technological change?—A case study from China. (January 2020) - Qiang, Ge
As the main achievement of Tibetan modernization in the 1970s, the promotion of winter wheat enabled wheat, which had rarely been planted in Tibet, to become the second-largest crop in the region. Surprisingly, Tibetan peasants, who at first had strongly resisted winter wheat, became active participants in just two or three years. During this process, how did the state change peasants' attitudes? How did the national government negate their resistance? Based on documents and oral history materials, this research study shows that political movement played a crucial role. First, the class struggle consisted of a crackdown on the resistance to new technologies and also promoting rural community differentiation so that mutual supervision among peasants neutralized 'weapons of the weak'. Second, the function of political movement in remolding belief and arousing affection inspired people's enthusiasm for growing wheat and their sense of political identity by portraying wheat as a symbol of emancipation. However, this movement also had certain side effects on production, and the whole project in the late 1970s was driven astray by blind political worship and neglect of realities.